Use of Rice Husk Ash for Copper, Chromium, Zinc, and Lead Bioremediation in Crude Oil-Contaminated Soil - Douglas, Reward Kokah; Fou, Ayebatin; Araka, Peremelade Perez (European Journal of Applied Sciences, 2022)
In this study, 1kg soil sample was artificially contaminated with 250ml crude oil and incubated for 4-day; and heavy metals-copper (Cu), chromium (Cr), zinc (Zn), and lead (Pb) concentrations were measured by flame atomic adsorption spectrometry (AAS) to be 11.68mg/kg, 38.96mg/kg, 59.34mg/kg, and 28.56mg/kg, respectively. Fresh rice hush ash (RHA = 0.5kg) was prepared from rice husk (RH) and used for the bioremediation of these metals in a 2-month experiment. The RHA reduced the Cu, Cr, Zn, and Pb concentrations by 33%, 29%, 27%, and 25%, respectively. Considering the quantity of RHA to the contaminated soil mass ratio (0.5:1.0), and the short period of the experiment (i.e., 2-month), RHA amendment is promising for the bioremediation of heavy metals polluted soils. This study provides the first reference point on the effectiveness of RHA for the remediation of heavy metals in polluted soils in the Niger Delta,Nigeria. Thus, we recommend field-trials and longer-term study to better assess the long-term applicability of this option for bioremediation of polluted soils.